2018
DOI: 10.1590/0103-8478cr20180151
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological quality of honey from stingless bee, jandaíra (Melipona subnitida), from the semiarid region of Brazil

Abstract: The aim of this study was to evaluate the presence of microorganisms in honey produced by the stingless bee (SB) jandaíra (Melipona subnitida) from the semiarid region of Brazil. Thirty-five samples were analyzed and all of them were positive for mesophilic bacteria, coliforms at 45°C, fungi, and yeast. Staphylococcus spp. were identified in 85.7%, while Bacillus spp. were detected in 34.3% of honey samples. DNAs of Clostridium perfringens and C. botulinum were detected in 40% and 2.8% of the samples, respecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Pinheiro et al . [72] mentioned the average count of fungi and yeast was 9.12×10 3 CFU/g for stingless bee honey in Brazil. In addition, Camargo et al .…”
Section: Resultsmentioning
confidence: 99%
“…Pinheiro et al . [72] mentioned the average count of fungi and yeast was 9.12×10 3 CFU/g for stingless bee honey in Brazil. In addition, Camargo et al .…”
Section: Resultsmentioning
confidence: 99%
“…The Bacillus genus predominance among the isolates agreed with other authors, who identified several species of Bacillus spp. in stingless bee species, such as Heterotrigona itama and Melipona subnitida [36,37]. Other authors also isolated Bacillus spp.…”
Section: Microorganism Dna Isolation From Honey and Pollen Of Stingle...mentioning
confidence: 99%
“…Aun cuando se sabe que es un alimento microbiológicamente seguro, se conoce poco de los microorganismos patógenos en mieles de abejas sin aguijón. Algunos estudios han demostrado la presencia no sólo de indicadores sanitarios sino también de algunos microorganismos patógenos en este tipo de mieles (3,4).…”
Section: Introductionunclassified